Rights And Obligations Of The Shareholder - Sharipov Asror Safar ugli (Global Scientific Publishing, 2024)
In this article, the concept of economic societies, their organizational legal differences in terms, rights and obligations of participants in society,methods for the implementation of these rights have been systematically analyzed. Also,the organizational legal mechanism of corporate governance has been researched and its the meaning and essence of the new concept, its elements are identified and scientific the novelty and practical significance are established, and in turn the experience of overseas studied
Keywords: economic societies; participatory; management